Conceptualising a Personal Capacity Development Framework for Senior Management Service in the Department of Defence - Ledwaba, Ncediwe Vivian (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMil)--Stellenbosch University, 2022.